Respon Mahasiswa Terhadap Panduan Publikasi Ilmiah untuk Program Studi Pendidikan Biologi Universitas Jambi: (Student Response toward Publication Guide for Biology Education Universitas Jambi) - Muhammad Yusuf; Agus Subagyo; Ali Sadikin (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
Student publications are one of the indicators of assessment in study program accreditation. Thus, efforts are needed to educate students to make these publications. This study aims to determine the response given by students to scientific publication guidelines that have been socialized. The research method used is qualitative research. The data in this study were obtained through filling out questionnaires by students as participants in the socialization of scientific publication guidelines. The results of this study indicate that students give a